SQL Server 2017 administration inside out - Assaf, William; West, Randolph; Aelterman, Sven; Curnutt, Mindy (Inside out (Redmond, Wash.), 2018)
SQL Server 2017 Inside Out is the authoritative in-depth reference for every working database administrator responsible for planning, implementing, or managing SQL Server in any production environment -- on-premises, cloud, or hybrid. Emphasising SQL Server 2017's newest features, including running SQL Server on Linux, four leading Microsoft database experts share insider techniques, solutions, advice, and troubleshooting tips for maximising efficiency and effectiveness in all facets of deployment and day-to-day administration, and performance optimisation. The authors tour a wide array of too.